An injectable hydrogel‐formulated inhibitor of prolyl‐4‐hydroxylase promotes T regulatory cell recruitment and enhances alveolar bone regeneration during resolution of experimental periodontitis. Issue 10 (19th August 2020) - Nagai, Kosuke; Ideguchi, Hidetaka; Kajikawa, Tetsuhiro; Li, Xiaofei; Chavakis, Triantafyllos; Cheng, Jing; Messersmith, Phillip B.; Heber‐Katz, Ellen; Hajishengallis, George
Abstract: The hypoxia‐inducible factor 1α (HIF‐1α) is critically involved in tissue regeneration. Hence, the pharmacological prevention of HIF‐1α degradation by prolyl hydroxylase (PHD) under normoxic conditions is emerging as a promising option in regenerative medicine. Using a mouse model of ligature‐induced periodontitis and resolution, we tested the ability of an injectable hydrogel‐formulated PHD inhibitor, 1, 4‐dihydrophenonthrolin‐4‐one‐3‐carboxylic acid (1, 4‐DPCA/hydrogel), to promote regeneration of alveolar bone lost owing to experimental periodontitis. Mice injected subcutaneously with 1, 4‐DPCA/hydrogel at the onset of periodontitis resolution displayed significantly increased gingival HIF‐1α protein levels and bone regeneration, as compared to mice treated with vehicle control. The 1, 4‐DPCA/hydrogel‐induced increase in bone regeneration was associated with elevated expression of osteogenic genes, decreased expression of pro‐inflammatory cytokine genes, and increased abundance of FOXP3 + T regulatory (Treg) cells in the periodontal tissue. The enhancing effect of 1, 4‐DPCA/hydrogel on Treg cell accumulation and bone regeneration was reversed by AMD3100, an antagonist of the chemokine receptor CXCR4 that mediates Treg cell recruitment. In conclusion, the administration of 1, 4‐DPCA/hydrogel at the onset of periodontitis resolution promotes CXCR4‐dependent accumulation of Treg cells and alveolar bone regeneration, suggesting a novel approach for regaining bone lost due to periodontitis.